Hubungan Lingkungan Fisik Rumah Dan Perilaku Hidup Bersih Dan Sehat Dengan Kejadian Ispa Pada Balita - Yulia, Yulia; Awalia, Fenny; Suharno, Suharno (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
Acute Respiratory Tract Infection (ARI) in Indonesia always ranks as the first cause of death and also often be the 10 most common diseases in hospitals and health centers. The aim of this research is to analyze the relationship between the physical environment of the house and Clean and Healthy Living Behavior with the incidence of ARI in toddlers. This research is analytical observational research with a cross-sectional approach. It was conducted in Matan Jaya Village, North Kayong Regency starting in June 2023 with a population aged 1 - â‰¤ 5 years of 114 toddlers and sample 53 respondents. The research found that ventilation 33.5%, lighting 54.7%, humidity 56.6%, residential density 77.4% did not meet the requirements, while temperature (71.7%) met the requirements. The behavior of not washing hands was 75.5%, and 79.2% of toddlers had family who smoked. Hence, there is a relationship between ventilation, lighting, humidity, residential density, hand washing and smoking behavior. There is no relationship between temperature and the incidence of ARI. It is recommended to open the windows of the house so there is air circulation and sunlight comes in, it can reduce the humidity and reduce the risk of suffering ARI.